Aplasia cutis congenita with hypocalvaria in a neonate - Rajendra Prasad Anne; Suresh Kumar Angurana; Renu Suthar; Akshay Kumar Saxena; Venkataseshan Sundaram (Indian Journal of Paediatric Dermatology, 2020)
We report a neonate presenting with a large scalp defect with hypoplasia of underlying frontal and parietal bones. It fits into the description of a severe form of aplasia cutis congenital with hypocalvaria.